Singing Training Through Choir for Students at Bahorok 1 Public High School - Kamaluddin Galingging; Ronald Heriko Saragih; Emmi Simangunsong; Elia Prischilia Tambunan (CV. Dharma Samakta Edukhatulistiwa, 2026)
The low level of vocal technique and choral harmony skills among students at Bahorok 1 Public High School made this community service activity urgent. Students had difficulty dividing their voices into soprano, alto, tenor, and bass (SATB), maintaining pitch accuracy, and understanding intervals, resulting in a lack of harmony. This activity aims to improve vocal competence, understanding of harmonization, and build cooperation and confidence among students through choir training. The implementation methods include initial observation, determining voice groups based on vocal characteristics, basic vocal technique training, training for each voice group using the drill method, and gradually combining all voices with guidance and guitar accompaniment. The results of the activity showed an improvement in students' ability to maintain pitch accuracy, understand SATB voice divisions, and produce more harmonious harmonization. In addition, students showed greater enthusiasm and confidence after being able to perform songs together. The impact of this activity not only improved musical skills but also strengthened discipline, concentration, and cooperation among students. Thus, choir training is effective as an effort to strengthen music arts capacity in schools and is recommended to be implemented continuously in extracurricular programs.